2022
DOI: 10.1093/ageing/afab241
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxes experienced by informal caregivers of people with dementia during the transition from home to a nursing home

Abstract: Background The transition from home to a nursing home is a common care process experienced by older persons with dementia and their informal caregivers. This transition process is often experienced as fragmented and is paired with negative outcomes for both older persons (e.g. mortality) and informal caregivers (e.g. grief). Due to the central role that informal caregivers play, it is crucial to capture their experiences throughout all phases of the transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Previous studies can be comparable to our study ndings in the sense of experiences navigating hospital-to-home transitions. In the broader context of transitions of care for older adults who require care across different settings, e.g., from hospital to home, home to hospital, hospital to a nursing home, etc., older adults and informal caregivers have similarly reported experiences indicating satisfaction, while others have reported a lack of person-centered care and negative care outcomes (8, 15,[31][32][33][34]. The varied experiences encountered during hospital-to-home transitions suggest the importance of assessing individual older adult health conditions and family dynamics and providing tailored practical information to address unique situations (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies can be comparable to our study ndings in the sense of experiences navigating hospital-to-home transitions. In the broader context of transitions of care for older adults who require care across different settings, e.g., from hospital to home, home to hospital, hospital to a nursing home, etc., older adults and informal caregivers have similarly reported experiences indicating satisfaction, while others have reported a lack of person-centered care and negative care outcomes (8, 15,[31][32][33][34]. The varied experiences encountered during hospital-to-home transitions suggest the importance of assessing individual older adult health conditions and family dynamics and providing tailored practical information to address unique situations (31).…”
Section: Discussionmentioning
confidence: 99%
“…The theme 'Locked in or locked away' involved transitions from home to a care home, which without the complexity of a pandemic have been found to be stressful and complex for informal caregivers [6,29]. Others have identified that while this transition can be relieving for informal caregivers, it is still emotionally draining [33]. Groenvynck et al [33] and Samsi et al [6] have found that caregivers can feel guilty for placing their care recipient in care home.…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified that while this transition can be relieving for informal caregivers, it is still emotionally draining [33]. Groenvynck et al [33] and Samsi et al [6] have found that caregivers can feel guilty for placing their care recipient in care home. It is now evident that COVID‐19 added an ‘all or nothing’ – aspect to care home transition decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The carer experience is widely reported as being complex and constituting multiple paradoxes, such as a sense of relief alongside guilt, or a need for respite but a desire to stay close (Crawford et al, 2015;Groenvynck et al, 2022;Høgsnes et al, 2014;Lee et al, 2022;McCormack et al, 2017;Cronfalk et al, 2017). Not all transitional experiences of informal carers of a person living with dementia are exclusively negative and often some positivity comes to light at the same time as acknowledging sadness (Johansson et al, 2014;Moon et al, 2017;Pritty et al, 2020;Rondon-Sulbaran et al, 2021).…”
Section: Transitions In Caring For a Person With Dementiamentioning
confidence: 99%